2015
DOI: 10.1038/srep13430
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrichment of mycobacterial proteins from infected host macrophages

Abstract: Upon infection, Mycobacterium tuberculosis (Mtb) deploys specialized secretion machinery to deliver virulent proteins with the capacity to modulate a variety of host-cellular pathways. Studies on the identification of intra-macrophage Mtb proteins, however, are constricted by an inability to selectively enrich these virulent effectors against overwhelming protein content of the host. Here, we introduce an Mtb-selective protein labeling method based on genetic incorporation of azidonorleucine (Anl) through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Identification of the BfrB Binding Protein in Human Macrophages-One of the effectors identified here, BfrB, was previously found to be required for Mtb survival in macrophages (41,51) and is enriched from infected macrophages (43), suggesting that BfrB may play an important role in the interaction with the host. To identify the macrophage binding partners of BfrB, we purified GST-tagged BfrB and incubated it with PMA-treated THP-1 lysate before performing GST pull-down and silver staining ( Fig.…”
Section: Screening Of Mtb Proteins That Interact With Macrophagementioning
confidence: 81%
See 2 more Smart Citations
“…Identification of the BfrB Binding Protein in Human Macrophages-One of the effectors identified here, BfrB, was previously found to be required for Mtb survival in macrophages (41,51) and is enriched from infected macrophages (43), suggesting that BfrB may play an important role in the interaction with the host. To identify the macrophage binding partners of BfrB, we purified GST-tagged BfrB and incubated it with PMA-treated THP-1 lysate before performing GST pull-down and silver staining ( Fig.…”
Section: Screening Of Mtb Proteins That Interact With Macrophagementioning
confidence: 81%
“…Previous work has suggested that bacterial proteins smaller than 70 KDa can cross the host phagosomal membrane (61). Although the exact mechanism by which BfrB secreted across the Mtb membrane to macrophage remains unclear (43,44), the disassembly of Mtb BfrB triggered by pupylation may be important in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEK293T cells were pulsed with 50µM myristic acid-azide (Life Technologies) for 24 hours and the incorporated azide moiety was conjugated to the alkyne immobilized on a matrix using the Click-iT protein enrichment kit (Life Technologies), as reported earlier (35). HA-tagged proteins in the enriched fraction were detected by immunoblotting.…”
Section: Myristic Acid Azide Pulse Labelling and Conjugationmentioning
confidence: 99%
“…Recently however, enrichment of bacterial secretomes using in vitro infection models was reported [92,93]. Both studies used biorthogonal labeling of bacterial proteins with ANL to isolate the secretome ( Figure 3B).…”
Section: Secretomics For Identifying Bacterial Extracellular Effectormentioning
confidence: 99%